The Family Album of General Pedro José Méndez - Pariente Fragoso, José Luis (Libros UAT, 2018)
The historical forge of Pedro José Méndez was marked in less than a decade, between 1857 and 1866, that is, from the age of majority at 21 April, until his heroic death when he was not yet 30 years old. The referred album is a fine sample of the social location of the Méndez family during the second third of the 19th century in the central region of Tamaulipas.